2015
DOI: 10.1021/acs.jproteome.5b00134
|View full text |Cite
|
Sign up to set email alerts
|

Human Metabolic Responses to Chronic Environmental Polycyclic Aromatic Hydrocarbon Exposure by a Metabolomic Approach

Abstract: The toxicities of polycyclic aromatic hydrocarbons (PAHs) have been extensively explored due to their carcinogenic and mutagenic potency; however, little is known about the metabolic responses to chronic environmental PAH exposure among the general population. In the present study, 566 healthy volunteers were dichotomized into exposed and control groups to investigate PAH-induced perturbations in the metabolic profiles. Nine urine PAH metabolites were measured by a sensitive LC-MS/MS method to comprehensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…In contrast, hs-CRP has been reported to be at most minimally associated with time of day [ 47 , 48 ]. Repeated measures and contrasting exposures within study participants was a strength where changes in measurements over time can be explored with partitioning of inter- and intra-individual variability [ 49 ], and may have provided analytical improvement over cross-sectional analyses for causal inference [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, hs-CRP has been reported to be at most minimally associated with time of day [ 47 , 48 ]. Repeated measures and contrasting exposures within study participants was a strength where changes in measurements over time can be explored with partitioning of inter- and intra-individual variability [ 49 ], and may have provided analytical improvement over cross-sectional analyses for causal inference [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental metabolomics has emerged as an approach for sensitively quantitating thousands of chemical signals in a biological sample, providing broad spectrum measurements of human metabolism that may be indicative of environmental chemicals [ 8 ]. Metabolomic perturbations have been associated with occupational air pollution exposures [ 9 , 10 ]. Walker, et al, employed high-resolution metabolomics (HRM), using sensitive liquid chromatography-mass spectrometry (LC-MS), coupled with advanced bioinformatics methods, as a platform linking exposure to internal doses and biological responses.…”
Section: Introductionmentioning
confidence: 99%
“…The biological mechanisms by which PAH and VOC metabolites exert effects on health outcomes are not well established but they have been shown to induce oxidative stress (Li et al, 2015; Wang et al, 2015). Two urinary markers of oxidative stress are 8-isoprostane, a measure of lipid peroxidation (Milne et al, 2005), and 8-hydroxy-2′-deoxyguanosine (8-OHdG), a measure of DNA oxidation (Evans et al, 2010; Poulsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, three studies reported evidence of potential PAH-related oxidative stress in children. A cross-sectional multicity study of schoolchildren in China and South Korea, reported an association between PAH exposure marker 1-hydroxypyrene and urinary malondialdehyde (MDA), a marker of oxidative stress (23), while a study of metabolomics responses to PAH exposure, which included children in the study population, found that PAH exposure was associated with altered markers of oxidative stress (24). A recent study observed a significant dose response relationship between the sum concentration of urinary monohydroxylated metabolites of PAHs and 8-hydroxy-2-deoxyguanosine (8-OHdG), a common biomarker of oxidative stress (25).…”
Section: Introductionmentioning
confidence: 99%